Analisis Tantangan dan Kelebihan Pembelajaran Berbasis Teknologi Informasi dan Komunikasi pada Kurikulum Merdeka di Sekolah Dasar - Asfiana Asfiana; Fitriyani Fitriyani; Mohamad Agung Rokhimawan (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
ICT-based learning in elementary schools refers to the integration of information and communication technology in the learning process. The government has adopted initiatives to bring ICT into the basic education curriculum. The population in this study consisted of teachers, students and related parties at Sekolah Dasar Negeri Maguwoharjo 1, Sleman Regency, Yogyakarta. The use of ICT allows wider access to distance learning, increases student learning motivation, makes it easier to understand material, and facilitates independent learning. Apart from that, teachers also find it easy to convey lesson material and minimize their shortcomings in coordinating the class. The use of ICT also provides easier access to learning resources, enriches learning, and facilitates the creation of important documents.Teachers need to address the challenges of technical preparation, device and internet accessibility, and changes in teaching methods. Schools must face the challenges of investment in ICT infrastructure, staff and teacher training, as well as unstable electricity issues. In facing these challenges, support from schools, teachers and other interested parties is very important to ensure the successful implementation of ICT-based learning.